New results about fuzzy γ-convex functions connected with the q-analogue multiplier-Noor integral operator - Ekram E. Ali; Miguel Vivas-Cortez; Rabha M. El-Ashwah (AIMS Mathematics, 2024)
The features of analytical functions were mostly studied using a fuzzy subset and a $ \mathfrak{q} $-difference operator in this study, as we investigate many fuzzy differential subordinations related to the $ \mathfrak{q} $-analogue multiplier-Noor integral operator. By applying fuzzy subordination to univalent functions whose range is symmetric with respect to the real axis, we create a few new subclasses of analytical functions. We define numerous classes related to the family of linear $ \mathfrak{q} $ -operators and introduce them. Here, we focus on the inclusion results and other integral features.